Five new species of Apobaetis Day (Ephemeroptera: Baetidae) and updated key to nymphs - Lima, Claudia R. T. De; Cruz, Paulo Vilela; Hamada, Neusa (Zootaxa, 2024)
This study focuses on the Baetidae family of Ephemeroptera, particularly the Pan-American genus Apobaetis Day, 1955, in Brazil. Baetidae is the second richest family in this order, with over 1100 species globally. Although extensively studied in Brazil, there is still a considerable Linnean deficit, emphasizing the need for further exploration and identification. This research reveals that in-depth studies of specific groups often lead to the discovery of new species and corrections to existing records, enhancing the accuracy of identification. We conducted a detailed study of Apobaetis resulting in the identification of five new species: A. dalcolmoae sp. nov., A. danielae sp. nov., A. nisiae sp. nov., A. sabinoae sp. nov., and A. trivellae sp. nov., each described here from nymphs and distinguished by specific morphological features. The study provides detailed comparisons with existing species, emphasizing characteristics such as maxillary palp, paraproct, glossa shape, and setae presence. We also propose an updated identification key to aid in the recognition of all Apobaetis species known in the nymphal stage. We also address the distribution of certain species in Brazil, pointing out potential misidentifications and the need for further revision. In conclusion, the research expands the known species within Apobaetis to 22. The findings underscore the importance of continuous taxonomic studies for accurate species identification and pave the way for future evolutionary research within this genus.